Increasing shot and data collection rates of the Shock/Shear experiment at the National Ignition Facility. (May 2016) - Doss, F. W.; Flippo, K. A.; Capelli, D.; Cardenas, T.; DeVolder, B.; Kline, J.; Kot, L.; Kurien, S.; Loomis, E.; Merritt, E. C.; Perry, T.; Schmidt, D.; et al.
Abstract: Updates to the Los Alamos laser-driven high-energy-density Shock/Shear mixing- layer experiment are reported, which have collectively increased the platform's shot and data acquisition rates. The strategies employed have included a move from two-strip to four-strip imagers (allowing four times to be recorded per shot instead of two), the implementation of physics-informed rules of engagements allowing for the maximum flexibility in a shot's total energy and symmetry performance, and splitting the laser's main drive pulse from a monolithic single pulse equal to all beams into a triply-segmented pulse which minimizes optics damage.